Regular STI testing amongst men who have sex with men and use social media is suboptimal – a cross-sectional study. (May 2017) - Frankis, Jamie; Goodall, Lisa; Clutterbuck, Dan; Abubakari, Abdul-Razak; Flowers, Paul
Sexually transmitted infections (STIs) disproportionately affect men who have sex with men, with marked increases in most STIs in recent years. These are likely underpinned by coterminous increases in behavioural risks which have coincided with the development of Internet and geospatial sociosexual networking. Current guidelines advocate regular, annual sexually transmitted infection testing amongst sexually active men who have sex with men (MSM), as opposed to symptom-driven testing. This paper explores sexually transmitted infection testing regularity amongst MSM who use social and sociosexual media. Data were collected from 2668 men in Scotland, Wales, Northern Ireland and the Republic of Ireland, recruited via social and gay sociosexual media. Only one-third of participants report regular (yearly or more frequent) STI testing, despite relatively high levels of male sex partners, condomless anal intercourse and high-risk unprotected anal intercourse. The following variables were associated with regular STI testing; being more 'out' (adjusted odds ratio = 1.79; confidence interval = 1.20–2.68), HIV-positive (adjusted odds ratio = 14.11; confidence interval = 7.03–28.32); reporting ≥10 male sex partners (adjusted odds ratio = 2.15; confidence interval = 1.47–3.14) or regular HIV testing (adjusted odds ratio = 48.44; confidence interval = 28.27–83.01). Men reporting long-term sickness absence from work/carers (adjusted odds ratio = 0.03; confidence interval = 0.00–0.48) and men aged ≤25 years (adjusted odds ratio = 0.36; 95% confidence interval = 0.19–0.69) were less likely to test regularly for STIs. As such, we identify a complex interplay of social, health and behavioural factors that each contribute to men's STI testing behaviours. In concert, these data suggest that the syndemics placing men at elevated risk may also mitigate against access to testing and prevention services. Moreover, successful reduction of STI transmission amongst MSM will necessitate a comprehensive range of approaches which address these multiple interrelated factors that underpin MSM's STI testing.